IMPACT OF GROSS DOMESTIC PRODUCT GROWTH ON BRAZILIAN NATIVE FORESTS: A COMPUTABLE GENERAL BALANCE ANALYSIS /Impacto do crescimento do Produto Interno Bruto sobre as florestas nativas brasileiras: uma análise de balanço geral computável - Suela, Attawan Guerino Locatel; Zanetti de Lima, Cicero; Wolf, Rayan; Michael Trotter, Ian (Informe GEPEC, 2023)
The Brazil is one of the world's leading producers and exporters of agricultural products, and it should continue to expand its production in the coming decades, remaining one of the main providers of food, fiber, and bioenergy for domestic and foreign consumption. This study aimed to analyze, by using Static Computable General Equilibrium model (BREA), the impacts on intermediate demand and the growth of agricultural production necessary for GDP to reach the expected projection for 2030, both for Brazilian macro-regions and for the MATOPIBA as well as the loss of native forest necessary for this happens. As a result, to compose the GDP growth in the North region, fruit growing would emerge with an increase of 9.2%. In MATOPIBA, soybean growth in suppressed forest areas showed an elevation of approximately 9.7%. It is observed that soy would continue to migrate to regions that hold cheap land and without the soybean moratorium embargo. The total amount of forests suppressed in Brazil for the expected economic growth to occur would be 490,000 ha. It is concluded that the economic growth related to the agricultural sectors is also linked to the conversion of native vegetation areas for future economic growth. Resumo: O Brasil é um dos principais produtores e exportadores mundiais de produtos agrícolas e deve continuar expandindo sua produção nas próximas décadas, mantendo-se como um dos principais fornecedores de alimentos, fibras e bioenergia para consumo interno e externo. Este estudo teve como objetivo analisar, por meio do modelo de Equilíbrio Geral Estático Computável (BREA), os impactos sobre a demanda intermediária e o crescimento da produção agrícola necessários para que o PIB atinja a projeção esperada para 2030, tanto para as macrorregiões brasileiras quanto para o MATOPIBA como bem como a perda de mata nativa necessária para que isso aconteça. Com isso, para compor o crescimento do PIB da região Norte, a fruticultura despontaria com crescimento de 9,2%. No MATOPIBA, o crescimento da soja em áreas de floresta suprimida apresentou uma elevação de aproximadamente 9,7%. Observa-se que a soja continuaria migrando para regiões que possuem terras baratas e sem o embargo da moratória da soja. A quantidade total de florestas suprimidas no Brasil para que ocorra o crescimento econômico esperado seria de 490.000 ha. Conclui-se que o crescimento econômico relacionado aos setores agropecuários também está atrelado à conversão de áreas de vegetação nativa para o crescimento econômico futuro.